Predicting Thermal Functional Performance of Protective Clothing Through Computer Simulations (Journal of Fiber Bioengineering and Informatics, 2008)
Previous simulations associated with the heat and moisture transfer behaviors of clothingare mainly expressed with mathematical models, relevant computational algorithms and numericalsolution methods and thus accessible to only a few professionals in the field. A software platform,called the S-smart system, was designed and developed as a friendly computer aided design tool withuser friendly interfaces for users with little/limited background knowledge of technical information,complex physics, mathematics and computational techniques. The purpose of this study is to reporta simulation test, using the S-smart system, for predicting the thermal functional performance ofpersonal protective clothing. The results pertaining to skin temperature, core temperature and humidityin the clothing microclimate between the chest wall and underwear were compared with experimentaldata. Good agreement, both in terms of the trends of changes and overall mean values, is observedbetween the two. Furthermore, 2D and 3D visualizations of the S-smart system seemed to providemore evidence that explains the heat and moisture transfer mechanisms and predicts thermal functionalperformance of clothing.
Keywords: computer simulation; S-smart system; personal protective clothing; thermal functions